Effects of a comprehensive warm-up program on performance parameters of elite and sub-elite male skiers - Çetin Sarışık, Derya; Şahin, Fatma Neşe (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study investigates the effects of a comprehensive warm-up program (FIFA 11+) on performance and injuries in ski athletes. Recent research shows that comprehensive warm-up programs can significantly affect performance and prevent injury. A total of 20 sub-elite (n:10) and elite (n:10) male ski athletes participated in the study. Inclusion criteria for the study were to be in the 18–25 age range and to have participated in international competitions for elite athletes and skiing for at least three years, as well as to be actively continuing their sports life for sub-elite athletes. A comprehensive warm-up program (FIFA 11+) was applied to the athletes three days a week, for eight weeks, before the training. Two measurements were taken from the athletes as pre-test and post-test. In this study, hexagon agility tests, high box tests, balance measurements, and proprioception measurement tests were applied. In the within-group comparisons, there was a statistically significant difference in the hexagon agility test (p = 0.01), proprioception test (p = 0.01), and high box test (p = 0.01). Dynamic right leg balance test (p = 0.01) was significant in the sub-elite athletes, and statistically significant differences were found among elite athletes in hexagon agility (p = 0.01), proprioception test (p = 0.01), high box test (p = 0.01), and the dynamic right leg balance test (p = 0.02). The effects of the FIFA 11+ warm-up protocol on performance parameters and proprioception did not differ between sub-elite and elite athletes.